Antibiofilm Formation Activities of Ethanol Extract of Curcuma domestica Val. Rhizome Against Multidrug-resistant Acinetobacter baumannii - Nasution, Halimah Raina; Yuandani; Abdi Wira Septama; Sony Eka Nugraha; Sufitni (International Journal of Science, Technology & Management, 2023)
Abstract. Multidrug resistance is still a major health problem worldwide. Biofilm formation was related to the resistance of bacteria mechanism. Acinetobacter baumannii, one of the bacteria that cause nosocomial infections, is given particular attention due to its high prevalence of resistance. The current study address observing the antibacterial activity and antibiofilm formation activity of Curcuma domestica rhizome extract against multidrug-resistant Acinetobacter baumannii (MDR A.baumannii). Curcuma domestica rhizome was macerated by ethanol 96%. Determination of Minimum Inhibitory Concentration (MIC) was carried out by the microdilution method. Antibiofilm formation analysis was determined by standard quantitative using crystal violet-stained assay. Ethanol extract of C. domestica possesses antibacterial activity against MDR A. baumannii with MIC value 250 µg/mL. Additionally, the ethanol extract of C. domestica could inhibit the biofilm formation of MDR A.baumannii, thus percentage of biofilm formed only 23.7% and significance different with control after analyzed using ANOVA post hoc test Tukey. According to these results, ethanol extract of C. domestica revealed antibacterial activity and had the potency in suppressing the biofilm formation of MDR A.baumannii, thus could be utilized in clinical application, especially in MDR A.baumannii infection. Keywords: Antibiofilm, antibacterial, Curcuma domestica, multidrug-resistant, Acinetobacter baumannii